Applicability of 3T Body MRI in Assessment of Nonfocal Bone Marrow Involvement of Hematopoietic Neoplasia in Dogs. (26th July 2013) - Feeney, D.A.; Sharkey, L.C.; Steward, S.M.; Bahr, K.L.; Henson, M.S.; Ito, D.; O'Brien, T.D.; Jessen, C.R.; Husbands, B.D.; Borgatti, A.; Modiano, J.
<x xml:space="preserve">Abstract</x> Background The utility of whole body magnetic resonance imaging (MRI) in detecting bone marrow infiltration in dogs with cancer has not been investigated. Objectives To assess the feasibility of 3T body MRI for bone marrow assessment in dogs with hematopoietic neoplasia. Animals Seven dogs with B‐cell lymphoma, 3 dogs with myelodysplastic syndrome (MDS), and 2 clinically normal dogs. Methods A prospective study of dogs with hematopoetic cancer was conducted using T1W, T2W, In‐Phase, Out‐of‐Phase and STIR pulse sequences of the body excluding the head prior to bone marrow sampling. The relative signal intensity of a midlumbar vertebral body and a midshaft femoral bone marrow was compared by visual and point region of interest analysis to regional skeletal muscle. Results Similarity of femoral diaphyseal and vertebral body marrow signal intensity to that of skeletal muscle on the Out‐of‐Phase sequence was useful in distinguishing the 3 dogs with hypercellular marrow because of MDS from the 7 dogs with B‐cell lymphoma and from the 2 clinically normal dogs. 1/7 dogs with lymphoma had proven bone marrow involvement but normal cellularity and less than 5% abnormal cells. Unaffected midfemoral marrow had greater signal intensity than skeletal muscle and unaffected vertebral marrow had less signal intensity than skeletal muscle on the Out‐of‐Phase sequence. Conclusions and Clinical Importance 3T, Out‐of‐Phase MR pulse sequence was useful in distinguishing diffuse bone marrow infiltrate (MDS) from minimally or unaffected marrow using skeletal muscle for signal intensity comparison on whole body MRI.